Nutritional profile and obesity: results from a random‑sample population‑based study in Córdoba, Argentina - Aballay, Laura Rosana (2015)
Fil: Aballay, Laura Rosana. Universidad Nacional de Córdoba. Facultad de Ciencias Médicas. Escuela de Nutrición. Estadística y Bioestadística; Argentina